Estudo da viabilidade de materiais metal-orgânicos como sorvente alternativo para a extração de pesticidas em mamão (Carica papaya) por MSPD - Barreto, Alysson Santos (2011)
Pesticides of different chemical and toxicological classes are used to control the pest attack on crops. However, treatment with these substances leave residues in the environment or the product itself, when used extensively, disregarding the ceilings set by law. The materials conventionally used in steps of extraction and preconcentration of pesticides in environmental matrices have a limited adsorption capacity or have low selectivity for specific analytes. Therefore, this study investigated the feasibility of metal-organic materials (MMO) as an alternative sorbent for the extraction of contaminants in papaya (Carica papaya). Such compounds form a new class of hybrid materials organic-inorganic porous stable, ordered, high surface area, which enables its application as pre-concentrators analytes and also in gas storage, molecular recognition and adsorption. The molecular formulas suggested for metal-organic materials were synthesized ∞[(La0,9Eu0,1)2(DPA)3(H2O)3], for the heteronuclear compound, and ∞[Eu(C14H4O8)(C2O4)3(H2O)2] for the homonuclear compound. The ligand coordination Na4ntc with Eu+3 ion in the homonuclear material occurred through the oxygen atoms of carboxylate groups attached to aromatic ring. In the case of heteronuclear compound, the ligand is coordinated to the metals H2DPA from the carboxylate oxygen atoms and nitrogen of pyridine. The luminescence spectroscopy studies of metal-organic material ∞[Eu(C14H4O8)(C2O4)3(H2O)2], indicated the presence of a single site symmetry around the lanthanide ion. Since the emission spectrum of ∞[(La0,9Eu0,1)2(DPA)3(H2O)3] indicated that the first coordination sphere of the metal has a low point group symmetry and has a single species broadcaster. According to data from X-ray diffraction single-crystal heteronuclear compound crystallized in monoclinic system with space group P21/c. The material formed a microporous threedimensional structure with channels that propagate along the crystallographic c axis. The extraction method developed enabled recovery of the pesticide pyrimethanil (52%). The elution solvent was chosen as ethyl acetate and the ratio matrix: adsorbent used was 1:3 (m / m).